Optimization of LPG Diffusion Flame Synthesis of CNT Structures using Statistical Design of Experiments (SDOE) - Rabinder Singh; Akash Deep; Jyoti Bharj; Nishtha Arya (Institute of Advanced Engineering and Science, 2012)
A statistical designed experimental approach was followed to investigate the various diffusion flame conditions for the synthesis of carbon nanotubed structures utilizing domestic Liquefied petroleum gas (IS – 4576) as the fuel carbon source. LPG flow rate, Oxygen flow rate, Height above burner (HAB) and Exposure time have been identified to generate different flame conditions based on varying One factor at a time (OFAT) approach. Two–level ‘full factorial’ design model in “Minitab12” software has been used for design of experiments. The 16 samples of soot with different flame conditions were collected on the surface of stainless steel plate. The output parameters i.e. weight of soot and substrate surface temperature were analyzed by Analysis of variance (ANOVA) to ensure that the experimentation is following the physics of the diffusion flame.Transmission electron microscope (TEM) images showed the growth of well aligned single walled carbon nanotubed structures with high aspect ratio as 220nm – 650nm diameter and 534nm – 1803nm length. In the present studythe parametric range for producing the single walled carbon–nanotubed structures through LPG diffusion flame have been found for optimization.